Evolutionary Computation for Classifier Assessment and Improvement - Correia, João Nuno Gonçalves Costa Cavaleiro (2018)
Thesis submitted to the University of Coimbra in partial fulfilment of the requirements for the Doctoral Program in Information Science and Technology